Aganone vescovo e la scrittura carolina a Bergamo alla metà del IX secolo: dinamiche ed eredità di un’innovazione culturale - De Angelis, Gianmarco (Scrineum, 2013)
The long-lasting episcopate of Aganone (837-867), a learned Frankish bishop strictly connected to the imperial court and to some of the most important intellectual of his time, represented a real turning point in Bergamo’s history during Early Middle Ages, both in political and social fields, and for a whole regarding cultural expressions. The paper aims at pointing out the connections between the process of the definitive strengthening of Carolingian power in town and the innovations verifiable in the local literacy, which since the very first times of Aganone is characterized by a sudden and uniform adherence to the Caroline minuscule canon, so overcoming the graphic particularism and the cursive writing tendencies of the previous period. The hypothesis that Aganone’s and his entourage’s installation in Bergamo coincided with the formation of a graphic ’school’ (or, at least, with the strong affirmation of an unitary cultural trend) seems to be confirmed by the appearance, in the subscriptions, of notae tachigraphicae and other special chancellery signs, which from bishop’s curia will spread later on also among notaries and other outstanding laymen, as a distinctive mark of urban élites.